STUDENTS’ RESPONSES TOWARD DRAMA PERFORMANCE SHOW - Ferry Wijaya Wijaya; Agung Suhadi (Teaching English and Language Learning English Journal, 2024)
The objective of this research is to find out how is the students‘ responses toward the drama subject that they studies and performed in their final semester test. The design of this research is Descriptive research. The subjects of this research are all English students of the fifth semester of English Education Study program of Muhammadiyah University of Bengkulu who have taken the drama subject and have performed the drama at their final semester test. They are 17 students. The instrument used in this research is a questioner about the students‘ responses adapted from Sagimin (2018). The questionnaire consists of 14 items of statements. There are 5 types of students‘ responses in the questionnaire. They are: strongly agree (SA), agree (A), neutral (N), disagree (DA), and strongly disagree (SDA). The data in this research were collected by: 1) making the google form link. 2) Distributing the questioner to the students via google form, 3) downloading the data from google form. The data in this research were analyzed by the following steps. They are as follows. 1) Checking the students‘ answers in google form, 2) Classifying the type of students‘ responses, 3) Analyzing the data with the percentage formula, 4) Discussing the data, and 5) Concluding the findings. The results showed that the data strongly supports the idea that students generally have positive feelings and experiences with the practical parts of the Drama course. The course seems to be successful in fostering creativity, script understanding, language improvement, and various other skills. This information is crucial for educators and curriculum planners to understand what aspects of the Drama course students enjoy, allowing for potential improvements in the future. The average percentage of student responses to the Drama Performance Show is reported to be 87%, falling within the "Very Good" category (81-100%). Key words: students’ responses, Drama Performance Show